Perceiving bad apples versus rotten trees: evidence from the exposure of politician misbehavior in Colombia (2020)
This paper studies the effects of disclosing information about politician misbehavior on trust in public institutions. I use news bulletins from the main anti-corruption agency in Colombia announcing disciplinary prosecutions against municipal mayors. I exploit the timing of the bulletin's publication as a source of variation on the information about the mayor's misbehavior. Using a difference-in-difference framework, I find citizens show a sophisticated use of the information to judge public institutions. News of the prosecution led to increased trust in judicial institutions. However, the effects on confidence in the political system depend on whether citizens perceive the prosecuted mayor as an individual transgressor or as representative of political institutions that are persistently led by questionable individuals. In the former case, the bulletin's publication increased support for the political system. In the latter, it diminished trust in the elections, in political parties, in Congress, and reduced overall support for the political system. These findings highlight the spillover effects of an institution's performance on the public's confidence in other democratic institutions.